Implementasi Struktur Naratif Greimas pada Cerita Ulat Entaduk (Sastra Lisan Melayu Mempawah): Implementation of The Greimas Narrative Structure on Ulat Entaduk Story (Oral Literature of Malay Mempawah) - Muhammad Asyura; Elsa Mulya Karlina; Effiyadi Effiyadi; Haries Pribady (Balai Bahasa Provinsi Papua, 2021)
This research is a qualitative study describing the narrative structure of Ulat Entaduk story as one among the oral literature (fable) living in Malay society in Mempawah. The source of this research data are two native speakers from Mempawah with data in the form of fable stories. The Data was analyzed with a literary study using Greimas narrative structure theory. The results of this study showed that the acution and functional schemes of Ulat Entaduk story is based off the inner conflict of the main character namely the mother and her childish adoptive son (blood-sucking worm) to torment the inner and physical mother. This happened because she too spoiled for her adoptive child that threatened her and family life. The most striking extrinsic element in the Caterpillar's story is self-immaturity and a family education that belongs to sex education. Readers are also taught to be thankful, respect for parents, and live independently as a key to the happiness of life.